Efficacy of Hepatic Resection vs. Radiofrequency Ablation for Patients With Very-Early-Stage or Early-Stage Hepatocellular Carcinoma: A Population-Based Study With Stratification by Age and Tumor Size - Jiang, Yi-Quan; Wang, Zi-Xian; Deng, Yi-Nan; Yang, Yang; Wang, Guo-Ying; Chen, Gui-Hua (Frontiers in Oncology, 2019)
Background: Because of the poor health conditions of elderly patients (age >65) with very-early-stage and early-stage hepatocellular carcinoma (HCC), primary treatment via hepatic resection (HR), or radiofrequency ablation (RFA) must be considered. However, few studies have examined this issue. Methods: A retrospective cohort was obtained from the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2015. Patients were grouped by tumor size (0–20, 21–30, 31–35, and 31–50 mm) and age (>65 and ≤65). Overall survival (OS) and disease-specific survival (DSS) were assessed. Results: In total, 1912 patients aged >65 and 2,784 patients aged ≤65 were analyzed after propensity score matching (PSM). For patients >65 with tumors ≤20 mm, OS and DSS did not differ significantly between the RFA and HR groups (p = 0.47 and p = 0.76, respectively). For patients with tumors measuring 21–30 mm, the HR group had better OS and a trend toward better DSS compared with the RFA group (p = 0.03 and p = 0.09, respectively). For patients with tumors measuring 31–50 mm, the HR group had better OS and DSS compared with the RFA group (p < 0.001 for both). For patients <65, the HR group had better OS and DSS compared with the RFA group for all tumor sizes. Conclusions: For elderly patients (age >65), RFA is recommended for tumors ≤20 mm. For patients older than 65 with tumors measuring 21–50 mm and for those younger than 65 with tumors of any size, HR is the better choice.